Answer:
c + 3d = 14.75
2c + 5d = 26
A box of candy is $4.25 and a drink is $3.50
Step-by-step explanation:
Let c represent the cost of a box of candy and let d represent the cost of a drink
c + 3d = 14.75
2c + 5d = 26
Solve by elimination by multiplying the top equation by -2
-2c - 6d = -29.5
2c + 5d = 26
Add them together
-d = -3.5
d = 3.5
Plug in 3.5 as d into one of the equations to solve for c
c + 3d = 14.75
c + 3(3.5) = 14.75
c + 10.5 = 14.75
c = 4.25
So, a box of candy is $4.25 and a drink is $3.50
Answer:
Step-by-step explanation:
take angle B as reference angle
using cosec rule
cosec B=hypotenuse/opposite
cosec B=13/12
cosec B=1.08
B=cosec 67
B=67 degree
for ratio,
cosec B=13/12
16.6 is the answer. 16 is the whole number so u just divide 3 and 5 and get .6
Answer:
Karla's 15 miles per week to Brad's 17 miles per week.
Step-by-step explanation:
First, we would need find the total number of miles each individual rides per week. We do this by dividing the total miles ridden by the number of weeks it took for each individual like so...
Karla: 135 / 9 = 15 miles per week
Brad: 102 / 6 = 17 miles per week
Finally, the comparison would be
Karla's 15 miles per week to Brad's 17 miles per week.
Answer:
1) x = (a+c)/b
2) The equation is correct no matter what value x takes.
Step-by-step explanation:
1) a−(a+b)x=(b−a)x−(c+bx)
<=> a - ax - bx = bx - ax - c - bx
<=> a - ax - bx - (bx - ax - c - bx) = 0
<=> a - ax - bx - bx + ax + c + bx = 0
<=> a - ax + ax - bx - bx + bx + c = 0
<=> a - bx + c = 0
<=> bx = a + c
If b ≠ 0, x = (a+c)/b
2) 2(3x−5a)+9(2a−7b)+3(5a−2x)=0
<=> 2×3x + 2×(-5a) + 9×2a + 9× (-7b) + 3×5a + 3×(-2x) = 0
<=> 6x -10a + 18a - 63b + 15a - 6x = 0
<=> (6x - 6x) + (15a - 10a + 18a) - 63b = 0
<=> 23a - 63b = 0
<=> 23a = 63b
=> a = 63b/23
with all values of x, the equation is correct.